2000
DOI: 10.1152/ajpheart.2000.278.4.h1261
|View full text |Cite
|
Sign up to set email alerts
|

Contractile and relaxing reactivity in carotid and femoral arteries of chicken embryos

Abstract: Contractile and relaxing reactivity in carotid and femoral arteries of chicken embryos. Am J Physiol Heart Circ Physiol 278: H1261-H1268, 2000.-In the embryo, hypoxemia causes redistribution of cardiac output from the periphery toward the heart and the brain. In view of this, we investigated developmental changes in the contractile and relaxing properties of the peripheral femoral artery (Fem) and the more central carotid artery (Car) at 0.7, 0.8, and 0.9 of the chicken embryo incubation time. Isolated arterie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 24 publications
(48 reference statements)
3
49
0
Order By: Relevance
“…Our group previously showed that the response to ACH in the femoral artery of the chicken embryo at the end of incubation is entirely endothelium-dependent (19). Precontraction with high K ϩ , blockade of NO synthase with L-NAME, and inhibition of cyclooxygenase with indomethacin are not sufficient to entirely block ACH-induced relaxation in the chicken embryo [this study and (19)] and adult chicken (24,25).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Our group previously showed that the response to ACH in the femoral artery of the chicken embryo at the end of incubation is entirely endothelium-dependent (19). Precontraction with high K ϩ , blockade of NO synthase with L-NAME, and inhibition of cyclooxygenase with indomethacin are not sufficient to entirely block ACH-induced relaxation in the chicken embryo [this study and (19)] and adult chicken (24,25).…”
Section: Discussionmentioning
confidence: 70%
“…Precontraction with high K ϩ , blockade of NO synthase with L-NAME, and inhibition of cyclooxygenase with indomethacin are not sufficient to entirely block ACH-induced relaxation in the chicken embryo [this study and (19)] and adult chicken (24,25). This indicates that besides NO, prostaglandins, and EDHF, an additional unknown factor contributes to the endotheliumdependent response in this species.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It is furthermore possible that protein cannot elicit a proper signal transduction cascade in the yolk sac, perhaps because a member of the downstream cascade is absent. This occurs in other receptor/ligand systems during embryonic development (LeNoble et al, 2000). It may also be that ephrin/Eph signaling in the yolk sac is already maximally active, and the added proteins, which were previously described as agonists in both neural and endothelial cells (Wang and Anderson, 1997;Füller et al, 2003) do not increase signal transduction.…”
Section: Discussionmentioning
confidence: 94%
“…To examine arteriolar contractility and relaxation behavior, resistance sized arterioles were isolated and mounted in a wire myograph as described previously (le Noble et al, 2000). To examine vasoconstriction, arterioles were challenged with norepinephrine (NE), phenylephrine (Phe) and angiotensin II (AngII).…”
Section: Measurement Of Flow Induced Remodeling and Arteriolar Contramentioning
confidence: 99%